Lipid Metabolic Pathways Confer the Immunosuppressive Function of Myeloid-Derived Suppressor Cells in Tumor - Yan, Dehong; Adeshakin, Adeleye O.; Xu, Meichen; Afolabi, Lukman O.; Zhang, Guizhong; Chen, Youhai H.; Wan, Xiaochun (Frontiers in Immunology, 2019)
Myeloid-derived suppressor cells (MDSCs) play crucial roles in tumorigenesis and their inhibition is critical for successful cancer immunotherapy. MDSCs undergo metabolic reprogramming from glycolysis to fatty acid oxidation (FAO) and oxidative phosphorylation leading to lipid accumulation in tumor. Increased exogenous fatty acid uptake by tumor MDSCs enhance their immunosuppressive activity on T-cells whereby promoting tumor progression. Tumor-infiltrating MDSCs in mice prefer FAO over glycolysis as their primary source of energy, and treatment with FAO inhibitors significantly improve anti-tumor immunity. This review highlights the immunosuppressive function of lipid accumulation and lipid signaling pathways in the context of MDSCs regulation of tumor microenvironment. The manipulation of these pathways can alter the function of these cells and therefore, could provide novel therapeutic approaches to enhance cancer immunotherapy.